Problems of translating English sentences into Uzbek - Sultonmurotova, Shakhrizoda Muzaffar qizi (Science and Education, 2023)
The present article is devoted to the investigation of various problems of translation, which are constantly suffered by language learners, and to present the ways of eliminating these crucial issues in translation process. The point of current paper is also to show the divergences of English and Uzbek languages and they can be cause for what kind of difficulties for translators.